Mineral Composition of Some Sweet Corn (Zea mays L. saccharata Sturt.) Genotypes Under Semi Arid Region - OKTEM, ABDULLAH (Asian Journal of Chemistry, 2010)
In this study, mineral contents of some sweet corn genotypes are determined. The research was carried out during 2003 and 2004 in Sanliurfa, Turkey. Eight hybrid and two open-pollinated sweet corn genotypes were grown in the field and kernel samples analyzed by an atomic absorption spectrometry. Some minerals such as K, Ca, Mg, Na, Fe, Mn, Cu and Zn were determined in kernel of sweet corn genotypes. Genotypes were statistically significant (**p < 0.01) for all minerals in both years. K and Ca content of open-pollinated genotypes were higher than hybrid values whereas Fe, Mn and Cu contents were lower than hybrid values. Mg, Na and Zn values were similar for hybrids and open-pollinated genotypes. Mineral composition of some genotypes such as Reward, Jubilee, Merit and Secerac were higher than other genotypes. According to correlation analysis, K and Ca were negative correlated with some micronutrients like Fe, Mn and Cu. Correlations among Fe, Mn and Cu were positive and significant.